Kurt Grote and Jens Kruppa at 75 m of the 100 m Breaststroke Race at the 1998 Goodwill Games in New York - Rushall, B. S. (1999)
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Kurt Grote and Jens Kruppa at 75 m of the 100 m Breaststroke Race at the 1998 Goodwill Games in New York. In this race Kurt Grote (the swimmer furthest away in each frame) recorded a time of 1:01.76, which was ranked third in 1998. Jens Kruppa (the closest swimmer) recorded a time of 1:1.79, which was ranked fifth in 1998.